Pengaruh Lingkungan Kerja, Kepuasan Kerja, dan Komunikasi Organisasi pada Kinerja Karyawan di Rri Medan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aLims to aLnaLlyze the influence of work environment, job saLtisfaLction, aLnd orgaLnizaLtionaLl communicaLtion on employee performaLnce aLt RaLdio Republik IndonesiaL (RRI) MedaLn. ALs aL naLtionaLl public broaLdcaLsting institution, RRI holds aL significaLnt responsibility in delivering aLccuraLte aLnd reliaLble informaLtion to the public. To caLrry out this role effectively aLnd efficiently, employee performaLnce plaLys aL criticaLl role. Employee performaLnce is influenced not only by individuaLl caLpaLbilities but aLlso by externaLl faLctors such aLs the work environment, job saLtisfaLction, aLnd orgaLnizaLtionaLl communicaLtion. This reseaLrch employs aL descriptive quaLntitaLtive aLpproaLch using staLtisticaLl daLtaL aLnaLlysis methods. The results of the study show thaLt, paLrtiaLlly, the vaLriaLbles of work environment aLnd job saLtisfaLction do not haLve aL significaLnt effect on employee performaLnce, with significaLnce vaLlues aLbove the aLlphaL threshold of 0.05. MeaLnwhile, the orgaLnizaLtionaLl communicaLtion vaLriaLble haLs aL significaLnt influence on employee performaLnce, with aL significaLnce vaLlue below 0.05. SimultaLneously, the three vaLriaLbles together haLve aL significaLnt effect on employee performaLnce aLt RRI MedaLn. These findings highlight the importaLnce of estaLblishing effective orgaLnizaLtionaLl communicaLtion systems aLnd improving the quaLlity of the work environment aLnd job saLtisfaLction in aL comprehensive maLnner. The results of this study aLre expected to serve aLs aL reference for RRI MedaLn’s maLnaLgement in formulaLting straLtegies to enhaLnce employee performaLnce through the development of aL conducive work environment, effective communicaLtion praLctices, aLnd improved employee welfaLre aLnd job saLtisfaLction.